Understanding religion: theories and methods for studying religiously diverse societies - Hedges, Paul (University of California Press, 2021)
Frontmatter -- CONTENTS -- ILLUSTRATIONS -- BOXES -- ACKNOWLEDGMENTS AND DEDICATIONS -- INTRODUCTION -- PART I WHAT IS RELIGION AND HOW TO APPROACH IT? -- 1 RELIGION Language, Law, and Legacies -- 2 METHOD Insider-Outsider Debates, Phenomenology, and Reflexivity -- 3 LIFE Lived Religion, Syncretism, and Hybridity -- PART II THEORIES, METHODOLOGIES, AND CRITICAL DEBATES -- 4 HISTORY Historical Methodology and the Invention of Tradition -- 5 POWER Social Constructionism, Habitus, and Authority -- 6 IDENTITY Social Identity Theory, In-Groups, Out-Groups, and Conflict -- 7 COLONIALISM Postcolonialism, Orientalism, and Decolonization -- 8 BRAINS The Cognitive Science of Religion and Beyond -- 9 BODIES Material Religion, Embodiment, and Materiality -- 10 GENDER Feminism, Sexuality, and Religion -- 11 COMPARISON Comparative and Contrastive Methodologies -- 12 RITUAL Ritualization, Myth, and Performance -- PART III RELIGIOUS DIVERSITY AND SOCIETY -- 13 DIVERSITY Religious Borders, Identities, and Discourses -- 14 DIALOGUE Interreligious Discourse and Critique -- 15 VIOLENCE Fundamentalism, Extremism, and Radicalization -- 16 SECULARISM Secularization, Human Rights, and Religion -- 17 GEOGRAPHY Place, the Lived Environment, and Environmentalism -- 18 POLITICS Governance, the Colonial Wound, and the Sacred -- GLOSSARY -- WHO'S WHO -- NOTES -- INDEX